Traces of Trinity signs, sacraments and sharing God's life - Robinson, Andrew (Andrew John Nottage) (Cambridge : James Clarke, 2014)
Traces of the Trinity is a masterful exploration of Christian theology through the lens of semiotics - the study of signs. Andrew Robinson provides helpful analogies and clear explanations throughout to lead even the non-specialist through the subject with ease. Although the variety of signs is endless, all signs and sign-interpretations have the same basic structure: sign, object and interpretation. Further, Robinson shows how this triad rests upon the existence of three 'elemental grounds': Quality, Otherness and Mediation. He proceeds to develop a highly original 'semiotic model' of the Trin.
Part I. The Trinity and the Structure of Signs -- 1. "You see a cloud rising" -- 2. Quality, otherness and mediation -- 3. The dance of meaning -- The colour of love -- Three kinds of relation -- Part II. Sharing God's Life -- 6. Partakers of the divine nature -- 7. Holding the baby -- 8. The joy of scapegoating -- 9. Holy, Catholic and Apostolic -- Part III. The Mystery of Existence -- 10.0Fingerprints of the Trinity -- 11. Life in the semiotic matrix -- 12. What God is not -- 13. Distinct but inseparable -- Summary -- Meditations.
CIP data; item not viewed.
Includes bibliographical references.
Master record variable field(s) change: 072
Keywords: Trinity; Semiotics -- Religious aspects -- Christianity; Philosophical theology; RELIGION -- Christian Theology -- General; RELIGION / Biblical Studies / Exegesis & Hermeneutics; Electronic books